2012
DOI: 10.1603/ec11096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soybean Varieties on Survival and Fecundity of Western Corn Rootworm

Abstract: The western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), is a major pest of corn (Zea mays L.) in North America and has evolved resistance to crop rotation by ovipositing in alternate crops such as soybeans [Glycine max (L.) Merr.]. Through experiments with plants grown in the greenhouse and the field, we tested whether soybeans with resistance to the soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), affected survival, fecundity, and consumption of soybean fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In the second type of control, 12 larvae in the late stage of the second instar and in the early stage of the third and final instar were placed into each bioassay container, and then the containers were placed in an incubator for 17 d, after which roots and soil were carefully searched by hand for larvae, pupae, and teneral adults. Larvae for this second control were from a nondiapausing strain of western corn rootworm and were reared to late second and early third instar on mats of maize seedlings (38). Instar was determined by visual inspection of head capsule width and body size using a dissection microscope.…”
Section: Methodsmentioning
confidence: 99%
“…In the second type of control, 12 larvae in the late stage of the second instar and in the early stage of the third and final instar were placed into each bioassay container, and then the containers were placed in an incubator for 17 d, after which roots and soil were carefully searched by hand for larvae, pupae, and teneral adults. Larvae for this second control were from a nondiapausing strain of western corn rootworm and were reared to late second and early third instar on mats of maize seedlings (38). Instar was determined by visual inspection of head capsule width and body size using a dissection microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid composition of leaf tissue from soybean lines with Rag1 genes is different than that of related plants lacking these genes [53]. Even so, consuming plant tissue from soybean lines with Rag genes did not alter fitness of western corn rootworm larvae ( Diabrotica virgifera virgifera LeConte) [54], and other studies [22,55] concluded that the presence of Rag1 genes had little impact on feeding (preference or defoliation) of several soybean pests within the Coleoptera and Lepidoptera, although in the latter study the authors documented reduced caterpillar growth rates. In contrast, Rich and Koch [23] found that brown marmorated stink bugs [ Halyomorpha halys (Stål)] preferred soybeans with Rag1 , and had lower levels of mortality when reared on pods from Rag1 plants.…”
Section: Discussionmentioning
confidence: 99%
“…() demonstrated that leaf tissue from Rag1 aphid‐resistant soybean retains resistance to A. glycines after detachment from plants. Furthermore, studies evaluating the effect of aphid‐resistant soybean on other insects have relied on detached plant tissue (Lundgren et al., ; Chandrasena et al., ; Dunbar & Gassman, ; Bruner et al., ). IA3027 and IA3027RA1 soybean were grown in 2014, using standard agronomic practices (Bennett et al., ; Kandel, ) and without insecticide application at the University of Minnesota Experiment Station (Saint Paul, MN, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Defoliating pests (i.e., Coleoptera and Lepidoptera) of soybean have shown a variety of responses in terms of preference and performance when subjected to aphid‐resistant soybean (Chandrasena et al., ; Dunbar & Gassman, ; Bruner et al., ). The response of H. halys or other North American species of stink bugs to aphid‐resistant soybean has not been reported.…”
Section: Introductionmentioning
confidence: 99%